2009
DOI: 10.1108/17542410910950877
|View full text |Cite
|
Sign up to set email alerts
|

A woman's place in hotel management: upstairs or downstairs?

Abstract: Purpose: This paper asks whether it is the notion of choice (a pro life work/life balance decision) that influences woman's desire to strive for promotion within a hotel organisation or is the choice made for female managers by a system of organisational processes. Findings:The interviews revealed that the perception of glass ceiling barriers faced by women differed depending on where they were in their career cycle. They were revealed as the 'long hours' culture, the Old Boy's network, hiring practices and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 45 publications
2
92
2
4
Order By: Relevance
“…Critical gender scholars, such as Holvino [34], observe that it is not possible to separate gender from color when considering women's participation in employment. This intersection is visible in New Zealand, where a disproportionately high number of Māori and Pacifica women occupy the lowest strata of service sector jobs [35] and where, in hospitality, European men are more likely to hold senior leadership positions [36,37]. Therefore, being a woman and/or belonging to a minority ethnicity group appears to negatively impact women's career possibilities and promotional processes, and stereotypical views on suitable roles penalize women and privilege men in the sector [38].…”
Section: Gender Employment and Sustainability In Tourismmentioning
confidence: 99%
“…Critical gender scholars, such as Holvino [34], observe that it is not possible to separate gender from color when considering women's participation in employment. This intersection is visible in New Zealand, where a disproportionately high number of Māori and Pacifica women occupy the lowest strata of service sector jobs [35] and where, in hospitality, European men are more likely to hold senior leadership positions [36,37]. Therefore, being a woman and/or belonging to a minority ethnicity group appears to negatively impact women's career possibilities and promotional processes, and stereotypical views on suitable roles penalize women and privilege men in the sector [38].…”
Section: Gender Employment and Sustainability In Tourismmentioning
confidence: 99%
“…Thus, Kanter highlighted the problems faced by women as 'token managers'; how men assigned to women stereotypical attributes and, through informal networking and other processes, 'closed ranks' against them -processes that continue to surface in more contemporary research (e.g. Benschop, 2009;Broadbridge, 2010a;Kumra, 2010;Kumra andVinnicombe, 2008, 2010;Mooney and Ryan, 2009;Personen, Tienari and Vanhala, 2009). While Kanter denied the salience of gender in her analysis -locating the dynamics observed within gender neutral organizational structuresshe arguably paved the way for future studies focusing not only on the detrimental experiences of women but also, from a critical perspective, on masculinity and men.…”
Section: Introductionmentioning
confidence: 99%
“…Peshave and Gupta (2017) opined career progression as "constant process of managing work, learning, leisure time transition in order to move upward towards a personally determined goal and creating self-preferred future". Summarizing the factors indicated by empirical research, long and irregular working hours, old boys" network, hiring practices, geographical mobility (Mooney, 2009;Marinakou, 2014;Brownell, 1993;Pathwardhan et al, 2015;Baum, 2015). Gender stereotypes, glass ceiling, cultural barriers, gender stereotype, dual role, visibility factor, gender segregation, lack of role models (Marinakou, 2014;Obadicand Ivana, 2009;Pathwardhan et al, 2015;Knox, 2008;Brownell, 1993) were found to be key barriers to career progression for women in the hotel industry.…”
Section: Introductionmentioning
confidence: 99%